Myroides Infection in a Baboon After Prolonged Pig Kidney Graft Survival. Issue 4 (May 2015) - Liu, Hong; Iwase, Hayato; Wijkstrom, Martin; Singh, Jagjit; Klein, Edwin; Wagner, Robert; Humar, Abhinav; Pasculle, William; Cooper, David K.C.
Abstract : Background: Immunosuppressed patients and experimental nonhuman primates are at risk of opportunistic infection. We report a Myroides spp. infection in an immunosuppressed baboon that had received a life-supporting kidney from a genetically engineered pig. Case Report: The baboon received a costimulation blockade-based immunosuppressive regimen as well as 2 anti-inflammatory agents (tocilizumab and etanercept). Although the pig kidney functioned well, approximately 4 months after the transplantation, the baboon became less active and ate and drank poorly. On day 136, it collapsed and died despite inotropic and fluid support. A blood culture drawn before death grew Myroides spp. Discussion and Conclusions: To our knowledge, Myroides spp. has not been reported as a cause of opportunistic infection in either patients with organ allotransplants or experimental animals. We summarize what is known about this rare organism and suggest it should be considered in any immunocompromised patient or animal. In the present case, we suggest the baboon died of circulatory shock following infection through an indwelling intravenous catheter.